SINTESIS DAN KARAKTERISASI FOTOKATALIS NANO TIO2-MEMBRAN POLIURETAN BERBASIS MINYAK ALPUKAT, HDI, DAN POLYETHYLENE GLYCOL (PEG) PADA FOTODEGRADASI METIL JINGGA - Arrazi, Abdul Hamid; Anwar, Devi Indah; Khumaisah, Lela Lailatul (Jurnal Inovasi Teknik Kimia, 2025)
Synthetic dyes such as methyl orange are classified as persistent pollutants that are difficult to degrade biologically, thus requiring effective and sustainable treatment technologies. This study develops a photocatalytic membrane based on polyurethane (PU) synthesized from avocado seed oil, hexamethylene diisocyanate (HDI), and polyethylene glycol (PEG) for immobilizing TiO₂ nanoparticles. PEG was used as a dispersing additive to prevent TiO₂ agglomeration and enhance the membrane's hydrophilicity. XRD characterization revealed that the TiO₂ nanoparticles were predominantly in the anatase phase, with a characteristic diffraction peak at 2θ = 25.2740°. FTIR analysis confirmed the successful synthesis of PU through the identification of characteristic functional groups, including –NH, –C=O (urethane carbonyl), and –C–O–C (ether) from PEG, as well as Ti–O and Ti–O–Ti vibrations indicating the presence of TiO₂. SEM observations showed a semi-globular morphology of TiO₂ particles that were homogeneously dispersed within the PU matrix without significant agglomeration. Photodegradation performance tests under UV-A irradiation (265 nm) at an irradiation distance of 11 cm demonstrated a maximum degradation efficiency of 91.165% at pH 4, with good reusability stability, achieving 91.173% efficiency after repeated cycles. The high effectiveness is attributed to electrostatic interactions between the positively charged TiO₂ surface and negatively charged methyl orange molecules, which accelerate the generation of reactive radical species during the photocatalytic process.